Huang Lian Jie Du decoction attenuated colitis via suppressing the macrophage Csf1r/Src pathway and modulating gut microbiota - Su, Shan; Liu, Ting; Zheng, Jia-Yi; Wu, Hai-Cui; Keng, Vincent W.; Zhang, Shi-Jie; Li, Xiao-Xiao (Frontiers in Immunology, 2024)
Ulcerative colitis, a subtype of chronic inflammatory bowel disease (IBD), is characterized by relapsing colonic inflammation and ulcers. Traditional Chinese herbal formulation Huang Lian Jie Du (HLJD) decoction is used clinically to treat diarrhea and colitis. However, the mechanism(s) associated with the effects of treatment remains unclear. This study aims to elucidate the molecular mechanistic effects of HLJD formulation on colitis. Chronic colitis in mice were induced by 1% dextran sulfate sodium (DSS) in drinking water continuously for 8 weeks, and HLJD decoction at the doses of 2 g/kg and 4 g/kg were administered orally to mice daily from the second week until experimental endpoint. Stool consistency scores, blood stool scores, and body weights were recorded weekly. Disease activity index (DAI) was determined before necropsy, where colon tissues were collected for biochemical analyses. In addition, the fecal microbiome of treated mice was characterized using 16S rRNA amplicon sequencing. HLJD decoction at doses of 2 g/kg and 4 g/kg relieved DSS-induced chronic colitis in mice by suppressing inflammation through compromised macrophage activity in colonic tissues associated with the colony stimulating factor 1 receptor (Csf1r)/Src pathway. Furthermore, HLJD formula could modify the gut microbiota profile by decreasing the abundance of Bacteroides, Odoribacter, Clostridium_sensu_stricto_1 and Parasutterella. In addition, close correlations between DAI, colon length, spleen weight and gut microbiota were identified. Our findings revealed that HLJD formula attenuated DSS-induced chronic colitis by reducing inflammation via Csf1r/Src mediated macrophage infiltration, as well as modulating the gut microbiota profile.